Hacker Tactic: Holding Data Hostage. - URBINA, IAN (New York Times, 2014)
The article focuses on a tactic of computer hackers by holding computer data as hostage until a fee is paid by the data owner and mentions topics including CryptoLocker ransomware, the U.S. Department of Justice, and countermeasures of companies to mislead data thieves.